Using servicescape to manage student commitment towards a higher education institution - Theron, E.; Pelser, A. (South African Journal of Higher Education, 2017)
Although a variety of approaches can be used to manage student commitment, the role of physical elements, such as a facility or institution’s virtual presence, appearance of infrastructure and signage, is often neglected in the literature. This gap in the literature is surprising considering the growing interest in the field of social sciences regarding the influence of physical elements (or tangibles) on commitment. It is against this background that this study investigated the possible effects of physical element attributes on student commitment. A number of antecedents of physical elements were identified by means of a literature review and their expected relationships with student commitment were proposed as hypotheses. These hypothesised relationships were assessed and a survey amongst 290 students from a multi-cultural South African university was conducted. The statistical program SPSS version 23 was used to analyse the data, and the hypothesised relationships were assessed by means regression analyses. The findings of the study indicate that the physical element dimensions ‘communicators’ and ‘virtual servicescape’ most significantly influenced overall student commitment. Contrary to popular belief, the study revealed that social servicescape did not have a significant impact on student commitment. Furthermore, it appears that a specific set of physical element attributes should be applied when student commitment is managed. Finally, the study offers an in-depth discussion of the theoretical and managerial implications of these findings for relationship marketing strategies.